Canadian Engaged Scholarship and the Russian War against Ukraine - Penelope C Sanz; Natalia Khanenko-Friesen (Engaged Scholar Journal, 2023)
In this issue, ESJ’s managing editor Penelope Sanz converses with Dr. Natalia Khanenko- Friesen, the founding editor of ESJ and now the director of the Canadian Institute of Ukrainian Studies (CUIS) at the University of Alberta, about engaged scholarship in the context of the Ukraine-Russia war. When this exchange took place in Spring 2023, the Israel-Palestine conflict the world is witnessing now was farthest from their minds. ESJ keeps in mind the peer reviewers and authors from these two countries, who submitted and/or evaluated articles on community-university engagements to the journal.